PENGARUH CAPITAL ADEQUACY RATIO, FINANCING TO DEPOSIT RATIO, DAN NON PERFORMING FINANCING TERHADAP RETURN ON ASSET PADA BANK UMUM SYARIAH (Studi Kasus pada Bank Umum Syariah di Indonesia Periode 2013 – 2017) - Tiara Diah Pitaloka; Djoko Kristianto; Bambang Widarno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This study aims to determine the effect of the variable influence of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Non Performing Financing (NPF) Against Return On Assets (ROA) in Sharia Commercial Banks found in Islamic Commercial Banks in Indonesia 2013 - 2017 period. The sample in this study were 7 samples of Sharia Commercial Banks in Indonesia for the 2013 - 2017 period that met predetermined criteria, which were taken using the Purposive Sampling method. This research uses secondary data types and uses multiple linear regression analysis techniques. Based on the results of the study indicate that partially Capital Adequacy Ratio (CAR) has no significant positive effect on Return On Assets (ROA). Financing to Deposit Ratio (FDR) has no significant negative effect on Return on Assets (ROA). Non Performing Financing (NPF) has a significant negative effect on Return on Assets (ROA). Simultaneously the Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) together have an effect on Return on Assets (ROA). The results of the Adjusted R Square value generated in this study are 0,959, meaning that as much as 96,6% of the dependent variation of Return on Assets (ROA) can be influenced by independent variables including Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) while 4,1% is influenced by other factors outside the variables studied.